ANALISIS SWOT-AHP DALAM MENENTUKAN STRATEGI PEMASARAN UNTUK MENINGKATKAN VOLUME PENJUALAN - Hadi, Ahmad Abdul; Hussein , Ananda Sabil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The growing globalization era has required businesses to adapt to the increasingly competitive markets. Hobi Amatir is a business that sells ornamental fish. The sales volume of this company was decreasing, requiring it to develop its marketing strategy and improve its service in order to survive the business competition. The objective of this case study is to design alternate marketing strategies and to determine the prioritized marketing strategies. The population and the sample serve as the informants. Here SWOT was used to analyze the business’ internal and external environments, while Analytical Hierarchy Process was used to measure the weight of each factor and prioritized marketing strategy. The Analytical Hierarchy Process consisted of objective tier (the prioritized marketing strategy for Hobi Amatir), Criterion tier (consumer, cost, convenience, and communication), and alternative tier (the weakness-opportunity strategy). The data was harvested observations, questionnaires, and interviews with six key informants considered knowledgeable and capable of handling the marketing. This study finds that, in criterion tier, consumer is the prioritized factor (0.408) and that, in alternative tier, handling the breeding and selling of predatory ornamental fish is the prioritized alternate strategy (0.300).